Penerapan Guided Imagery untuk Menurunkan Intensitas Nyeri pada Pasien Post Operasi Sectio Caesarea - Thessara, Shafira Octafia Ramadani; Jerau, Emiliani Elsi; Septiani, Febi (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Cesarean section often causes postoperative pain that can hinder maternal recovery and comfort. Guided imagery, a non-pharmacological relaxation technique, can be used to help reduce pain and improve well-being. Objective: This community service to implement the guided imagery as a non-pharmacological method to reduce postoperative pain in cesarean section patients. Method: This community service activity was carried out in the inpatient ward of Purwokerto Islamic Hospital on July 9–25, 2025, by demonstrating guided imagery techniques to 27 post-cesarean section patients aged 17–35 years with mild to moderate pain levels.  The guided imagery intervention was conducted for three consecutive days, with each session lasting 15 minutes, covering relaxation, breathing focus, visualization of a calming place, and positive affirmations, using leaflets as a guide. Pain levels were measured before and after each session using a Numeric Rating Scale (NRS) to assess changes in pain intensity. Result: The results showed that before the intervention, the majority of participants on the first day experienced moderate pain, 21 participants (77.8%) on the first day and 23 participants (85.2%) on the second day while 20 participants (74.1%) reported mild pain on the third day. After applying guided imagery, the proportion of patients with moderate pain decreased to 18 participants (66.7%) on the first day, 22 participants (81.5%) reported mild pain on the second day, and by the third day all participants (100%) experienced only mild pain. Conclusion: These findings confirm that guided imagery is an effective non-pharmacological intervention for reducing postoperative pain in cesarean section patients, promoting greater comfort and supporting faster recovery.